Challenges and Opportunities in Qualitative Research Sharing Young Scholars' Experiences - Tsang, Kwok Kuen.; Liu, Dian.; Hong, Yanbi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book shares young scholars' (current PhD students and those who completed their PhD between 2010 and 2015) experiences with conducting qualitative social research. Intended as a guide for newcomers to the field, it focuses on the practical issues encountered by qualitative researchers rather than methodological discussions. Accordingly, it addresses a range of representative issues in the qualitative research process - namely research design, data access, data collection, and data analysis - and covers a variety of social sciences topics.
1 Introduction: Qualitative Research Methods in Empirical Social Sciences Studies - Young Scholar's Perspectives and Experiences -- 2 Starting Literature Review in Qualitative Research: An Illustration using the Mirror Effect -- 3 A Han Researcher in a Muslim Village: How to Enter the Field and Participants' Heart -- 4 Fieldwork in the Workplace: An Experience Entering in the Japanese Advertising Industry -- 5 Participant Selection and Access in Case Study Research -- 6 Discrepancy Reduction: Conducting Focus Group with Senioe Citizens in Hong Kong -- 7 Problems and Coping Strategies in Conducting Comparative Research in School Bullying between China and Norway -- 8 From Theories to Practicalities: Doing Cross-Cultural Research Fieldwork in Early Childhood Education and Care (ECEC) -- 9 Conducting Collaborative Action Research: Challenges and Coping Strategies -- 10 Coding with Storyline Approach: Recommendations to Cope with Challenges of Qualitative Data Analysis -- 11 A Researcher, a Container, or Both? A Stance of a Research in a Qualitative Research with Bereaved Children -- 12 Conclusion: Research Dilemma and Feasible Strategies.
Keywords: Sociology -- Methodology; Educational sociology; International education .; Comparative education; Sociological Methods; Sociology of Education; International and Comparative Education